2009
DOI: 10.1007/s10593-009-0297-4
|View full text |Cite
|
Sign up to set email alerts
|

4-Hydroxy-2-quinolones. 154*. Pyrimidin- 2-ylamides of 1-r-4-hydroxy-2-oxo-1,2-dihydro- quinoline-3-carboxylic acids. synthesis, structure, and properties

Abstract: Keywords: 2-aminopyrimidine, 1-R-4-hydroxy-2-oxo-1,2-dihydroquinoline-3-carboxamides, bromination, antitubercular activity, X-ray structural analysis.Pyrimidine bases occur in a number of the most widespread heterocyclic systems in nature. Occurring in nucleic acids and coenzymes these compounds play a direct role in encoding and transmitting hereditary information, in the metabolism of carbohydrates and lecithin, and also in many biochemical processes important for animals and plants [2]. As a result, natural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
6
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 18 publications
2
6
0
Order By: Relevance
“…However, the pyrazine fragment unexpectedly shows only two singlets of one proton (H-3) and two protons (H-5 and H-6) where in the latter case the signals at least for H-5 and H-6 should be observed as two separate doublets with a characteristically small α-pyridine type vicinal spin-spin coupling. Similarly to the 1-R-4-hydroxy-2-oxo-1,2-dihydroquinoline-3-carboxylic acid pyrimidin-2-ylamides we have previously reported [18], treatment of pyrazin-2-ylamides 1 with saturated 1-N-alkyl substituents in glacial acetic acid medium with molecular bromine gives light-orange crystalline precipitates which are evidently the perbromides 3a-m. 2-Aminopyrazines can be halogenated in the para position to the amino group [19] so subsequent refluxing of the reaction mixture (as in the case of the pyrimidin-2-ylamides [18]) would logically be expected to brominate the amide part of the molecule, i.e. to convert the perbromides 3a-m to the 5-bromopyrazin-2-ylamides of the corresponding quinoline-3-carboxylic acids.…”
supporting
confidence: 52%
See 2 more Smart Citations
“…However, the pyrazine fragment unexpectedly shows only two singlets of one proton (H-3) and two protons (H-5 and H-6) where in the latter case the signals at least for H-5 and H-6 should be observed as two separate doublets with a characteristically small α-pyridine type vicinal spin-spin coupling. Similarly to the 1-R-4-hydroxy-2-oxo-1,2-dihydroquinoline-3-carboxylic acid pyrimidin-2-ylamides we have previously reported [18], treatment of pyrazin-2-ylamides 1 with saturated 1-N-alkyl substituents in glacial acetic acid medium with molecular bromine gives light-orange crystalline precipitates which are evidently the perbromides 3a-m. 2-Aminopyrazines can be halogenated in the para position to the amino group [19] so subsequent refluxing of the reaction mixture (as in the case of the pyrimidin-2-ylamides [18]) would logically be expected to brominate the amide part of the molecule, i.e. to convert the perbromides 3a-m to the 5-bromopyrazin-2-ylamides of the corresponding quinoline-3-carboxylic acids.…”
supporting
confidence: 52%
“…It should be noted here that the 1-R-4-hydroxy-2-oxo-1,2-dihydroquinoline-3-carboxylic acid hetarylamides do not survive gas column chromatography without destruction hence we could not carry out the corresponding chromato-mass spectrometric analysis. As is known, under electron impact ionization the primary degradation of the molecular ions for this type of compounds occurs via a ketene [18]. In the example we are discussing, this behavior is retained but the bromine is found exclusively in the ketene fragment 6b with m/z 293/295.…”
mentioning
confidence: 83%
See 1 more Smart Citation
“…However, on the other hand, a monocrystal of the amido ester was grown from solution, which proved suitable for X-ray diffraction crystallographic structural analysis, and important information was obtained on the three-dimensional study of this class of compounds. As expected, many specific structural features were found common for primary N-R-amides of 4-hydroxy-2-oxo-1,2-dihydroquinoline-3-carboxylic acids [26][27][28]. Thus, in particular, amido ester 4 gives rise to an analogous system with strong intramolecular hydrogen bonds: 4-OH···O=C-NH and 6-C=O···HNC=O, which accounts for the existence of only the amide tautomer in the crystal, while the pyridine ring, carbamide group, and benzimidazole fragment lie in a single plane.…”
supporting
confidence: 72%
“…Comparing the data for preliminary screening (Table 3) with the results of a study of the antituberculosis properties for others diazahetarylamides of 1-R-4-hydroxy-2-oxo-1,2-di-hydroquinoline-3-carboxylic acids, we found that the benzimidazole derivatives had significantly higher activity than compared to pyrimidine analogs [28]. On the other hand, our products were inferior to pyrazin-2-ylamides [31] both in their capacity to repress the growth of a test strain and relative to the minimal inhibiting concentration (MIC) determined only for the most active samples.…”
mentioning
confidence: 94%